Implementation of Village SDGs in Achieving Sustainable Development Goals in Bali Province - Andari, Luh Gita (Jurnal Bali Membangun Bali, 2021)
Purpose: This study aims to determine village SDGs (SDGs desa) in accelerating the goals of sustainable development in the province of Bali from the indicators of Dana Desa (village fund) and IDM (Indeks Membangun Desa/village development index) Update. Research methods: This research is a qualitative descriptive study. Descriptive statistic research is used to describe phenomena in the conduct of research. Qualitative analysis is used to provide a description in the form of words to the results of the research Results and discussion: SDGs Desa that have been implemented in the Province of Bali have Supported the Sustainable Development Goals and Bali has become the first rank in the National Development Village Index Implication: SDGs Desa is one of the supporters of accelerating the achievement of sustainable development goals in Bali Province.